ASSESSMENT OF WATER QUALITY PARAMETERS AND THEIR CORRELATIONS IN THE KEMAMBANG RIVER, SIDOARJO, EAST JAVA PROVINCE: A ONE HEALTH FRAMEWORK APPROACH - Navratilova , Frisda Desyana; Munfarida, Ida; Oktorina, Sarita (Lingkar: Journal of Environmental Engineering, 2024)
The river, a vital resource for agricultural, industrial, and domestic use, faces pollution pressures from anthropogenic activities. This study examines the water quality parameters of the Kemambang River in Sidoarjo, East Java, within the context of the One-Health Framework, emphasizing the interconnectedness of environmental, human, and animal health. Sampling conducted at three distinct points along the river revealed spatial variability in key parameters such as Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), temperature, and oil and grease content. Analysis showed that while pH remained within acceptable limits, BOD and oil and grease levels exceeded regulatory standards, particularly downstream, where domestic and agricultural runoff contributed to oxygen depletion. Spearman correlation analysis highlighted strong positive correlations between TSS, COD, and oil and grease, while BOD and COD were negatively correlated with DO, underscoring the impact of pollutants on oxygen dynamics. These findings demonstrate how industrial and domestic activities compromise the river's ecological health, impacting human and aquatic systems. By adopting the One-Health Framework, this study provides a holistic perspective on water quality challenges, offering insights for targeted interventions and sustainable management practices.